Clinical Characteristics of Rheumatoid Arthritis Patients in Malang: Where Are We Now According to the Treat-to-Target Strategy? - Pratama, Mirza Zaka; Suryana, Bagus; Megawanto, Nurhandi (Universitas Brawijaya, 2023)
Background: Rheumatoid arthritis (RA) is the most frequent type of systemic inflammatory arthritis. Aim: to observe RA patients' clinical characteristics in Malang and assess the adherence of the clinical data to the existing guideline for the treat-to-target (T2T) strategy. Methods: This survey included 111 RA patients who visited the Rheumatology Clinic at Saiful Anwar Hospital in Malang. Patient's demographic information, medical and drug history, body mass index (BMI), tender joint count (TJC), swollen joint count (SJC), visual analogue scale (VAS) for pain, erythrocyte sedimentation rate (ESR), anti-cyclic citrullinated protein (CCP), and rheumatoid factor (RF) were all collected. The disease activity score for 28 joints - ESR (DAS28-ESR) was used to assess disease activity and remission. Results: The mean duration of the disease was 2.9±1.6 years. Among those patients, four patients (3.6%) got disease remission, and two patients (1.8%) had low activity. Methotrexate (MTX) was given to all subjects for an average of 78.4±11.7 months at a dose of 9.5±2.8 mg/week. Six patients (5.4%) received the DMARD combination of MTX+LEF (4.5%) and MTX+SSZ (0.9%). Most subjects had delayed MTX initiation (mean duration 6.0±2.2 months after the first onset); 77 patients (69.3%) initiated their MTX after >6 months since the first onset. Most subjects got 7.5 mg/weeks (45.0%), while only 11.7% of patients had ≥15 mg/weeks of MTX. Conclusion: The remission rate of RA patients in Malang is still low, which can be caused by inadequate adherence to the relevant guidelines and T2T strategy in clinical practices.